PENGARUH ARUS DAN WAKTU PADA PELAPISAN NIKEL DENGAN ELEKTROPLATING UNTUK BENTUK PLAT - Sutomo, Sutomo -; Senen, Senen -; Rahmat, Rahmat - (Universitas Diponegoro, 2010)
The influence of electric current and time using to coating production with electroplating machine for flat forming. Corrosion is the mainly problem of material, base on this problem researcher would like to know the influence of nickel’s mass for plat coating. This research have conclusion that more time the electric current is needed will produce more thickness of coating. The current is 4 amperes and the time is 2400 seconds will produce 1.8 gr nickel’s coating. Increasing current density will increase the thickness of coating, especially for using time 2400 seconds, current density 8.5 amperes/dm2. Layering rate of coating is 1.0 μm/second for current density A/dm2 Key word : electroplating, electric current, time coating